1H-Imidazol-4(5H)-ones and thiazol-4(5H)-ones as emerging pronucleophiles in asymmetric catalysis - Mielgo, Antonia; Palomo, Claudio (Beilstein Journal of Organic Chemistry, 2016)
Asymmetric catalysis represents a very powerful tool for the synthesis of enantiopure compounds. In this context the main focus has been directed not only to the search for new efficient chiral catalysts, but also to the development of efficient pronucleophiles. This review highlights the utility and first examples of 1H-imidazol-4(5H)-ones and thiazol-4(5H)-ones as pronucleophiles in catalytic asymmetric reactions.
Keywords: asymmetric catalysis; bifunctional catalysts; 1H-imidazol-4(5H)-ones; pronucleophiles; thiazol-4(5H)-ones

Catalytic Asymmetric Synthesis - Ojima, I. (John Wiley & Sons, 2010)

Catalytic Methods in Asymmetric Synthesis: Advanced Materials, Techniques and Applications - Gruttadauria, M.; Giacalone, F. (John Wiley & Sons, 2011)

New Frontiers in Asymmetric Catalysis - Mikami, K.; Lautens, M. (John Wiley & Sons, 2007)

Modern Synthetic Methods - Seebach, D.; Hungerbühler, E. (Synthesis of Enantiomerically Pure Compounds (EPC-Synthesis), 1980)

(untitled) - Liu, Y.; Han, S.-J.; Liu, W.-R.; Stoltz, B. M. (Acc. Chem. Res., 2015)

(untitled) - Hong, A. Y.; Stoltz, B. M. (Eur. J. Org. Chem., 2013)

(untitled) - Das, J. P.; Marek, I. (Chem. Commun., 2011)

(untitled) - Bella, M.; Gasperi, T. (Synthesis, 2009)

(untitled) - Cozzi, P. G.; Hilgraf, R.; Zimmerman, N. (Eur. J. Org. Chem., 2007)

(untitled) - Trost, B. M.; Jiang, C. (Synthesis, 2006)

Quaternary Stereocenters: Challenges and Solutions for Organic Synthesis - Christoffers, J.; Baro, A. (Wiley-VCH, 2005)

(untitled) - Douglas, C. J.; Overman, L. E. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Hawner, C.; Alexakis, A. (Chem. Commun., 2010)

(untitled) - Rathke, M. W.; Cowan, P. J. (J. Org. Chem., 1985)

(untitled) - Rathke, M. W.; Nowak, M. (J. Org. Chem., 1985)

(untitled) - Tirpak, R. E.; Olsen, R. S.; Rathke, M. W. (J. Org. Chem., 1985)

(untitled) - Yost, J. M.; Garnsey, M. R.; Kohler, M. C.; Coltart, D. M. (Synthesis, 2009)

(untitled) - Zhou, G.; Lim, D.; Coltart, D. M. (Org. Lett., 2008)

(untitled) - Alonso, D. A.; Kitagaki, S.; Utsumi, N.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2008)

(untitled) - Kohler, M. C.; Yost, J. M.; Garnsey, M. R.; Coltart, D. M. (Org. Lett., 2010)

(untitled) - Tan, B.; Hernández-Torres, G.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2012)

(untitled) - Fisk, J. S.; Mosey, R. A.; Tepe, J. J. (Chem. Soc. Rev., 2007)

(untitled) - Alba, A.-N.; Ríos, R. (Chem. – Asian J., 2011)

(untitled) - Hewlett, N. M.; Hupp, C. D.; Tepe, J. J. (Synthesis, 2009)

(untitled) - Trost, B. M.; Dogra, K.; Franzini, M. (J. Am. Chem. Soc., 2004)

(untitled) - Huang, H.; Zhu, K.; Wu, W.; Jin, Z.; Ye, J. (Chem. Commun., 2012)

(untitled) - Morita, A.; Misaki, T.; Sugimura, T. (Tetrahedron Lett., 2015)

(untitled) - Trost, B. M.; Hirano, K. (Angew. Chem., Int. Ed., 2012)

(untitled) - Qiao, B.; An, Y.; Liu, Q.; Yang, W.; Liu, H.; Shen, J.; Yan, L.; Jiang, Z. (Org. Lett., 2013)

(untitled) - Misaki, T.; Kawano, K.; Sugimura, T. (J. Am. Chem. Soc., 2011)

(untitled) - Misaki, T.; Jin, N.; Kawano, K.; Sugimura, T. (Chem. Lett., 2012)

(untitled) - Lu, N.; Wang, H. (Int. J. Quantum Chem., 2013)

(untitled) - Liu, Q.; Qiao, B.; Chin, K. F.; Tan, C.-H.; Jiang, Z. (Adv. Synth. Catal., 2014)

(untitled) - Jin, N.; Misaki, T.; Sugimura, T. (Chem. Lett., 2013)

(untitled) - Wang, T.; Yu, Z.; Hoon, D. L.; Huang, K.-W.; Lan, Y.; Lu, Y. (Chem. Sci., 2015)

(untitled) - Morita, A.; Misaki, T.; Sugimura, T. (Chem. Lett., 2014)

(untitled) - Zhao, D.; Wang, L.; Yang, D.; Zhang, Y.; Wang, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Han, Z.; Yang, W.; Tan, C.-H.; Jiang, Z. (Adv. Synth. Catal., 2013)

(untitled) - Misaki, T.; Takimoto, G.; Sugimura, T. (J. Am. Chem. Soc., 2010)

(untitled) - Xu, M.; Qiao, B.; Duan, S.; Liu, H.; Jiang, Z. (Tetrahedron, 2014)

(untitled) - Chen, W.; Hartwig, J. F. (J. Am. Chem. Soc., 2014)

(untitled) - Duan, S.; Li, S.; Du, N.-N.; Tan, C.-H.; Jiang, Z. (J. Org. Chem., 2015)

Amino Acids, Peptides and Proteins in Organic Chemistry - Hughes, A. B. (Wiley-VCH, 2009)

(untitled) - Cativiela, C.; Díaz de Villegas, M. D. (Tetrahedron: Asymmetry, 2007)

(untitled) - Cativiela, C.; Ordóñez, M. (Tetrahedron: Asymmetry, 2009)

(untitled) - Ohfune, Y.; Shinada, T. (Eur. J. Org. Chem., 2005)

(untitled) - Vogt, H.; Bräse, S. (Org. Biomol. Chem., 2007)

(untitled) - Monsey, R. A.; Fisk, J. S.; Tepe, J. J. (Tetrahedron: Asymmetry, 2008)

(untitled) - Bera, K.; Namboothiri, I. N. N. (Asian J. Org. Chem., 2014)

(untitled) - Kawakami, T.; Sasaki, T.; Reid, P. C.; Murakami, H. (Chem. Sci., 2014)

(untitled) - Fisk, J. S.; Monsey, R. A.; Tepe, J. J. (Chem. Soc. Rev., 2007)

(untitled) - Metrano, A. J.; Miller, S. J. (J. Org. Chem., 2014)

(untitled) - Tomohara, K.; Yoshimura, T.; Hyakutake, R.; Yang, P.; Kawabata, T. (J. Am. Chem. Soc., 2013)

(untitled) - Etxabe, J.; Izquierdo, J.; Landa, A.; Oiarbide, M.; Palomo, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Alemán, J.; Milelli, A.; Cabrera, S.; Reyes, E.; Jørgensen, K. A. (Chem. – Eur. J., 2008)

(untitled) - Jiang, H.; Paixão, M. W.; Monge, D.; Jørgensen, K. A. (J. Am. Chem. Soc., 2010)

(untitled) - Balaguer, A.-N.; Companyó, X.; Calvet, T.; Font-Bardía, M.; Moyano, A.; Rios, R. (Eur. J. Org. Chem., 2009)

(untitled) - Wang, Z. D.; Sheikh, S. O.; Zhang, Y. (Molecules, 2006)

(untitled) - Malerich, J. P.; Hagihara, K.; Rawal, V. R. (J. Am. Chem. Soc., 2008)

(untitled) - Zhu, Y.; Malerich, J. P.; Rawal, V. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hu, K.; Lu, A.; Wang, Y.; Zhou, Z.; Tang, C. (Tetrahedron: Asymmetry, 2013)

(untitled) - Seebach, D.; Sting, A. R.; Hoffmann, M. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Calaza, M. I.; Cativiela, C. (Eur. J. Org. Chem., 2008)

(untitled) - Konnert, L.; Reneaud, B.; Marcia de Figueiredo, R.; Campagne, J.-M.; Lamaty, F.; Martinez, J.; Colacino, E. (J. Org. Chem., 2014)

(untitled) - Arshad, N.; Hashim, J.; Kappe, C. O. (J. Org. Chem., 2009)

(untitled) - Bepary, S.; Youn, I. K.; Lim, H.-J.; Lee, G. H. (Eur. J. Org. Chem., 2012)

(untitled) - Farley, A. J. M.; Standford, C.; Dixon, D. J. (J. Am. Chem. Soc., 2015)

(untitled) - Monge, D.; Jiang, H.; Alvarez-Casao, Y. (Chem. – Eur. J., 2015)

(untitled) - Desimoni, G.; Faita, G.; Quadrelli, P. (Chem. Rev., 2015)

(untitled) - Byrd, K. M. (Beilstein J. Org. Chem., 2015)

(untitled) - Palomo, C.; Oiarbide, M.; García, J. M. (Chem. Soc. Rev., 2012)

(untitled) - Badiola, E.; Fiser, B.; Gómez-Bengoa, E.; Mielgo, A.; Olaizola, I.; Urruzuno, I.; García, J. M.; Odriozola, J. M.; Razkin, J.; Oiarbide, M.; Palomo, C. (J. Am. Chem. Soc., 2014)

(untitled) - Khalil, N. A.; Ahmed, E. M.; El-Nassan, H. B. (Med. Chem. Res., 2013)

(untitled) - Grummt, U.-W.; Weiss, D.; Birckner, E.; Beckert, R. (J. Phys. Chem. A, 2007)

(untitled) - Véniant, M. M.; Hale, C.; Hungate, R. W.; Gahm, K.; Emery, M. G.; Jona, J.; Joseph, S.; Adams, J.; Hague, A.; Moniz, G.; Zhang, J.; Bartberger, M. D.; et al. (J. Med. Chem., 2010)

(untitled) - Täuscher, E.; Weiß, E.; Beckert, R.; Fabian, J.; Assumpção, A.; Görls, H. (Tetrahedron Lett., 2011)

(untitled) - Yu, F.; Hu, H.; Gu, X.; Ye, J. (Org. Lett., 2012)

(untitled) - Géant, P.-Y.; Urban, M.; Remeš, M.; Císařová, I.; Veselý, J. (Eur. J. Org. Chem., 2013)

(untitled) - Zhang, H.; Wang, B.; Cui, L.; Li, Y.; Qu, J.; Song, Y. (Org. Biomol. Chem., 2014)

(untitled) - Wu, W.; Huang, H.; Yuan, X.; Zhu, K.; Ye, J. (Chem. Commun., 2012)

(untitled) - Zhu, K.; Huang, H.; Wu, W.; Wei, Y.; Ye, J. (Chem. Commun., 2013)

(untitled) - Barzen, S.; Rödl, C. B.; Lill, A.; Steinhilber, D.; Stark, H.; Hofmann, B. (Bioorg. Med. Chem., 2012)

U.S. Patent - Shaffer, J. E.; Thomson, S. A. (Oxathi(SIV)azol-5-one compounds, 1992)

(untitled) - Diosdado, S.; Etxabe, J.; Izquierdo, J.; Landa, A.; Olaizola, I.; López, R.; Palomo, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Okino, T.; Hoashi, Y.; Takemoto, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Schreiner, P. R.; Wittkopp, A. (Org. Lett., 2002)

(untitled) - Zhang, Z.; Schreiner, P. R. (Chem. Soc. Rev., 2009)

Hydrogen Bonding in Organic Synthesis - Kotke, M.; Schreiner, P. R. ((Thio)urea Organocatalysts, 2009)

(untitled) - Tan, B.; Lu, Y.; Zeng, X.; Chua, P. J.; Zhong, G. (Org. Lett., 2010)

(untitled) - Lippert, K. M.; Hof, K.; Gerbig, D.; Ley, D.; Hausmann, H.; Guenther, S.; Schreiner, P. R. (Eur. J. Org. Chem., 2012)

(untitled) - Semetey, V.; Rognan, D.; Hemmerlin, C.; Graff, R.; Briand, J.-P.; Marraud, M.; Guichard, G. (Angew. Chem., Int. Ed., 2002)

(untitled) - Sureshbabu, V. V.; Patil, B. S.; Venkataramanarao, R. (J. Org. Chem., 2006)

(untitled) - Myers, A. C.; Kowalski, J. A.; Lipton, M. A. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Semetey, V.; Hemmerlin, C.; Didierjean, C.; Schaffner, A.-P.; Giner, A. G.; Aubry, A.; Briand, J.-P.; Marraud, M.; Guichard, G. (Org. Lett., 2001)

(untitled) - Clayden, J.; MacLellan, P. (Beilstein J. Org. Chem., 2011)

(untitled) - Enders, D.; Lüttgen, K.; Narine, A. A. (Synthesis, 2007)

(untitled) - Lu, X.; Zhang, C.; Xu, Z. (Acc. Chem. Res., 2001)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Ye, L.-W.; Zhou, J.; Tang, Y. (Chem. Soc. Rev., 2008)

(untitled) - Cowen, B. J.; Miller, S. J. (Chem. Soc. Rev., 2009)

(untitled) - Trost, B. M.; Li, C.-J. (J. Am. Chem. Soc., 1994)

(untitled) - Trost, B. M.; Li, C.-J. (J. Am. Chem. Soc., 1994)

(untitled) - Trost, B. M.; Dake, G. R. (J. Org. Chem., 1997)

(untitled) - Zhang, C.; Lu, X. (Synlett, 1995)

(untitled) - Chung, Y. K.; Fu, G. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Sinisi, R.; Sun, J.; Fu, G. C. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Smith, S. W.; Fu, G. C. (J. Am. Chem. Soc., 2009)

(untitled) - Sun, J.; Fu, G. C. (J. Am. Chem. Soc., 2010)

(untitled) - Lundgren, R. J.; Wilsily, A.; Marion, N.; Ma, C.; Chung, Y. K.; Fu, G. C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Wang, T.; Yao, W.; Zhong, F.; Pang, G. H.; Lu, Y. (Angew. Chem., Int. Ed., 2014)

Iridium Catalysis - Hartwig, J. F.; Pouy, M. J. (Iridium-Catalyzed Allylic Substitution, 2011)

(untitled) - Tossati, P.; Nelson, A.; Marsden, S. P. (Org. Biomol. Chem., 2012)

(untitled) - Krautwald, S.; Sarlah, D.; Schafrofth, M. A.; Carreira, E. M. (Science, 2013)

(untitled) - Liu, W.-B.; Reeves, C. M.; Virgil, S. C.; Stoltz, B. M. (J. Am. Chem. Soc., 2013)